2008
DOI: 10.1353/hsj.2008.0003
|View full text |Cite
|
Sign up to set email alerts
|

Student and Stakeholder Perceptions of the Transition to High School

Abstract: A mixed method, longitudinal design was used to assess student and stakeholder perceptions of the transition to high school. Comparisons between parent and student perceptions revealed few differences and both groups were generally optimistic about entering the Freshmen Center. Following the transition, student perceptions exhibited important changes that point to a need for clarifying the academic, social, and organizational similarities and differences between the two grade levels. Interviews with school sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 19 publications
1
32
0
2
Order By: Relevance
“…This move across schools settings brings with it changes that can have positive or negative effects on students, hence transition to secondary school is a social and academic turning point for adolescents (Langenkamp, 2009;Smith, Akos, Lim & Wiley, 2008).…”
Section: Why and How Transition Is Seen As Criticalmentioning
confidence: 99%
See 1 more Smart Citation
“…This move across schools settings brings with it changes that can have positive or negative effects on students, hence transition to secondary school is a social and academic turning point for adolescents (Langenkamp, 2009;Smith, Akos, Lim & Wiley, 2008).…”
Section: Why and How Transition Is Seen As Criticalmentioning
confidence: 99%
“…Less maternal control was associated with more unsupervised activities (Laird & Marrero, 2011). Smith et al (2006Smith et al ( , 2008 found that American students below 9 th Grade looked forward to increased independence in choosing courses and developing an academic plan. As they were unlikely to appreciate the gravity of particular curriculum choices, guidance counsellors and parents played a significant role.…”
Section: Family-school Connectionsmentioning
confidence: 99%
“…For example, studies have found that students expressed fewer academic concerns in 9th grade than in 8th grade (Benner and Graham 2007; Smith et al 2008). Moreover, some evidence indicates that students’ academic attitudes do not suffer the disruptions observed in academic behaviors.…”
Section: Current Knowledge On the Transition To High Schoolmentioning
confidence: 99%
“…Coffey (2013) acknowledges the impact of the potentially different learning styles which secondary school promotes, and other authors have noted the differences in the curriculum (Tobell 2003). Whilst there is evidence that teachers are more concerned with academic issues at transfer (Topping 2011), pupils are more focused on socioemotional issues (Topping 2011) and potential bullying (Lucey and Reay 2000;Smith et al 2008;Rice, Frederickson, and Seymour 2011), and were also found to grieve for their lost primary friends (Coffey 2013). This research evidence suggests that the prioritisation of social and emotional coping skills (Jordan, McRorie, and Ewing 2010) and resilience (Lyons and Woods 2012), prior to secondary school transfer, would be beneficial for many children.…”
Section: The Primary/secondary Transitionmentioning
confidence: 97%